Effectiveness of a red cell antigen‐matching transfusion protocol in sickle cell disease patients. (15th November 2016) - Dezan, M. R.; Oliveira, V. B.; Bianchi, J. V. S.; Rodrigues, V.; Solano, J. H.; Gomes, F. C.; Bonifácio, S. L.; Levi, J. E.; Guallandro, S. F. M.; Krieger, J. E.; Pereira, A. C.; Sabino, E. C.; et al.
Abstract : Background and objectives: To date, it is unclear whether antigen matching is effective in reducing antibody development and whether transfusing blood from non‐Caucasian donors reduces alloimmunization in sickle cell disease patients (SCP). This study was designed to evaluate the effectiveness of an antigen‐matching strategy supplied by a mixed donor population, in reducing alloimmunization in SCPs. Methods: Eighty SCPs transfused with C‐, E‐ and K‐matched units and 2000 donors were genotyped for the most relevant RBC antigens, and resulting genotypic frequencies were compared. Also, alloantibodies specificity and clinical complications were evaluated in SCPs. Results: A high alloimmunization rate was observed despite the prophylaxis protocol (62·1%). The main cause underlying lack of effectiveness was transfusion of non‐matched units in external hospitals. Even though our donor population was ethnically mixed, it still exhibited antigenic differences in relation to SCPs (C and Fy a ). Frequency of clinical complications was similar between alloimmunized and non‐alloimmunized patients. Conclusions: Prospective antigen matching is an unattractive alloimmunization prophylaxis for SCPs if not associated with strategies to minimize the hazards related to transfusions at non‐index hospitals. Even in a highly mixed donor population, antigenic discrepancies in SCPs are high, increasing the risk of antibody development.